A Static Traffic Grooming Scheme for IP over WDM Optical Internet. Issue 2 (June 2014) - Lai, Wuwen; Wang, Longfei; Wang, Xingwei; Huang, Min
In order to improve the bandwidth utilization of IP over WDM (Wavelength Division Multiplexing) optical Internet, a static traffic grooming scheme was proposed by introducing the knowledge of fuzzy mathematics and microeconomics. It introduced the user traffic request delay satisfaction degree and the network relative cost. With the help of gaming analysis and layered graph, based on predatory search algorithm (PSA), it tried to find the optimal grooming solution with the comprehensive user QoS (Quality of Service) satisfaction degree maximized and the network relative cost minimized. It was simulated over actual network topologies and its performance was compared with certain existing traffic grooming scheme. Simulation results have shown that it is both feasible and effective with better performance.